The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.appdev.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Adopted children's language difficulties and their relation to symptoms of reactive attachment disorder: FinAdo study

Abstract: This study investigated the potential association between symptoms of reactive attachment disorder and language difficulties among internationally adopted children in Finland (the FinAdo study). The language difficulties were assessed using a standardised Five to Fifteen (FTF) parental questionnaire and the symptoms of reactive attachment disorder using a FinAdo questionnaire. The study sample consisted of 689 6-15 year old children (49.2% boys, response rate 48%). Twenty-nine percent of the children were repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
(79 reference statements)
1
3
0
Order By: Relevance
“…Therefore, scores at or above the 90th percentile in the child's gender and age group were used as cut-offs for being at risk of language difficulties (hereafter: difficulties) (see supplementary table S5). This is in agreement with the procedure used in studies using the original FTF questionnaire where a score above the 90th percentile marks the threshold for clinical concern [39].…”
Section: Language Developmentsupporting
confidence: 87%
“…Therefore, scores at or above the 90th percentile in the child's gender and age group were used as cut-offs for being at risk of language difficulties (hereafter: difficulties) (see supplementary table S5). This is in agreement with the procedure used in studies using the original FTF questionnaire where a score above the 90th percentile marks the threshold for clinical concern [39].…”
Section: Language Developmentsupporting
confidence: 87%
“…77 In addition, intellectual disabilities, language problems, and learning difficulties all have been identified in school-aged children with RAD and DSED. [80][81][82][83][84] A number of studies in older children and adolescents also have begun to explore the neurobiology of RAD and DSED. For example, Tottenham et al 85 studied 4-to 17-yearold children with histories of institutional rearing by presenting them with images of mother versus stranger and recording amygdala activation during functional magnetic resonance imaging (fMRI) scanning.…”
Section: Emerging Data In Older Childrenmentioning
confidence: 99%
“…Studies of the specific family factors that affect adopted children's experience in their families provide conflicting results. Some studies reveal family size or sibling composition being a significant factor (Beckett et al, 1999;Helder et al, 2016) while other studies demonstrate a lack of significance (Castle et al, 2009;Raaska et al, 2013). Of note, previous literature examining specific family factors and adopted children's outcomes have not used self-report, adoptedchild data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has examined specific family factors related to adopted children's adjustment but not the other members of the family. These studies provide conflicting results of the relationship between family factors and adopted child outcomes, such that some studies report no relationship between family size, sibling composition, or sibling spacing on adopted child outcomes (Castle et al, 2009;Raaska et al, 2013) while other studies report that adoptive families with biologically related children are more likely to experience adoption disruption or other negative outcomes (Beckett et al, 1999). One study found that smaller family size, homeschooling, being the only adopted child, and a parenting approach that encouraged age-appropriate behavior predicted improved cognitive outcomes in adopted children (Helder et al, 2016).…”
Section: Adoptive Family Factors and Outcomesmentioning
confidence: 99%